The Effect of Internal Audit and Accounting Information System on Financial Management of Bumdes with Internal Control System as a Moderating Variable: An Empirical Study of Bumdes in Villages in Kabila District, Bone - Sri Entin I. Lakoro; Usman; Ayu Rakhma Wuryandini (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the effect of internal audit and accounting information systems on the financial management of Village-Owned Enterprises (BUMDes) with the internal control system as a moderating variable in BUMDes in Kabila Bone District, Bone Bolango Regency. This study uses a quantitative approach with primary data obtained through questionnaires. The population in this study were all BUMDes managers in Kabila Bone District consisting of commissioners, supervisors, directors, secretaries, and treasurers of BUMDes. The research sample consisted of 32 respondents determined using a purposive sampling technique. The data analysis technique used Partial Least Squares–Structural Equation Modeling (PLS-SEM) through the SmartPLS version 4 application. The results of the study indicate that internal audit has a positive and significant effect on BUMDes financial management. The accounting information system also has a positive and significant effect on BUMDes financial management. The internal control system is unable to moderate the effect of internal audit on BUMDes financial management, so it is categorized as homologizer moderation. Conversely, the internal control system significantly moderates the effect of the accounting information system on BUMDes financial management, thus representing pure moderation. The findings of this study indicate that the success of BUMDes financial management is influenced not only by internal audits and accounting information systems but also by the effectiveness of the internal control system in strengthening the implementation of the accounting information system.